1950
DOI: 10.1680/macr.1950.2.4.39
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of vibrations in freshly placed concrete

Abstract: Descriptions are given of the electronic apparatus and techniques developed at the Road Research Laboratory for measuring vibrations. The equipment had been used, in the first instance, for measuring the movements produced in freshly placed concrete by an experimental vibrator operating on the surface. Details are given of the circuits, the calibration arrangements, and the type of information obtainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1954
1954
1973
1973

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…the frequency of vibration divided by the forward speed of travel) , and the force on the concrete. The maximum thickness of the slab which can be properly compacted is related to the product of these three factors (24) i ( 25) It was also found that the compaction varied with the depth and the consistency of the mix. The limiting value of the depth of compaction was foxind to be about 12 inches.…”
Section: Studies Involving Surface Vibrationmentioning
confidence: 99%
“…the frequency of vibration divided by the forward speed of travel) , and the force on the concrete. The maximum thickness of the slab which can be properly compacted is related to the product of these three factors (24) i ( 25) It was also found that the compaction varied with the depth and the consistency of the mix. The limiting value of the depth of compaction was foxind to be about 12 inches.…”
Section: Studies Involving Surface Vibrationmentioning
confidence: 99%